Peran Pengajar dalam Memotivasi Mahasiswa untuk Menentukan Judul Tugas Akhir: Studi Kasus Jurusan Sastra China Universitas Bina Nusantara - Endang Ernawati (Bina Nusantara University, 2012)
Article clarified the roles of a leaner in motivating students to achieve their final reports, especially in determining their research’s titles. Studi applied library research to find out some theories and concepts related to scientific writing, and data analysis on the research titles determined by the two classes of the Chinese department who took Chinese Scientific Writing on the past odd semester 2010/2011. Research results indicated that there was a duplication of the research titles and the static choice of titles because the lecturer did not give a clear literature study for the students, such as information retrieval to find previous research having the same topics, as well as practicing to read scientific publication in the forms of thesis, articles, and research reports. Moreover, there is a lack of reading habit, writing skills, and information retrieval skills that the students had performed. It can be concluded that a cooperation between lecturer and students to develop a better learning materials, to improve teaching methods, and interaction between lecturer and students in Chinese Scientific Writing subject so that the students are able to determine a proper titles, as an indicator that they have a clear description for their research activities.